Study on a GMV Compensator Design for Hierarchical-type Control in Plastic Processing Machinery - Takahiro SUGAHARA; Shin WAKITANI; Toru YAMAMOTO; Takashi OCHIIWA; Hideki TOMIYAMA (Nihon Kikai Gakkai ronbunshu)
Model-Based Development (MBD) has been widely adopted as an efficient product development methodology in the industrial world. A hierarchical-type control structure has been proposed as the control system architecture for products developed through MBD. In this control system, a compensator is introduced to mitigate the degradation of control performance caused by disturbances and model errors present in actual plants. This paper proposes a compensator design method based on Generalized Minimum Variance Control (GMVC). The proposed method is designed to suppress the influence of equation errors in the plant, which are represented by the CARIMA model. Additionally, the nominalization characteristics of the proposed method are discussed. The effectiveness of the proposed method is verified through numerical simulations, and its practicality is demonstrated through experiments using a slider-crank system applying the hierarchical-type control structure incorporating the proposed compensator.